Impact of Foreign Direct Investment and Information Communication Technology on Economic Growth: An Empirical Analysis from Selected Developing Countries - Dr. Rubeena Tashfeen,; Dr. Syed Muhammad Amir Shah,; Muhammad Sadil Ali,; Wasif Anis, (Al-Qanṭara, 2022)
In this research, we investigate the imperative role of foreign direct investment and information and communication technology on economic growth in selected developing countries by using panel data from 2004 to 2019. GDP per capita is used as the dependent variable, and foreign direct investment, information and communication technology, urban population, and exports are taken as independent variables. The study has used the random effect technique to find a link between variables. The study's findings show that foreign direct investment, information and communication technology, and urban populations have all played important roles in determining and enhancing economic growth in a number of developing countries. It is recommended that the government should provide more economic and political stability to encourage high exports and attract more foreign direct investment in these economies. Keywords: FDI, ICT, GDP, and Developing Countries